Plant-based diets among students at Rhodes University, South Africa: prevalence, motivations, and barriers - Andersson, Coral; Thondhlana, Gladman (Frontiers in Sustainable Food Systems, 2025)
In the context of unsustainable food choices and consumption patterns, transition to plant-based diets is considered a pathway to reducing greenhouse gas emissions. The youths, and university students in particular, represent a distinctive demographic group with great potential to follow plant-based diets, but limited knowledge concerning the prevalence and motivations of plant-based diets exists in the Global South. The aim of this study this research was to examine the prevalence of, motivations for and barriers to plant-based diets among Rhodes University students in South Africa. A total of 300 students responded positively to an online questionnaire survey. About 31% of the survey students followed a plant-based diet but this figure dropped to 18% when flexitarians were excluded from the analysis, with more females than males reporting so. The leading motivation for following plant-based diets was animal welfare concerns, followed by environmental sustainability, personal health, influence of family and friends, taste preference, saving money and sensory issues. There was a significant positive association between values relating to the environment - respecting the earth and protecting the environment and following a plant-based diet. Key barriers to plant-based diets reported included perceived high costs and lack of knowledge on plant-based diets. Interventions for promoting plant-based diets should make explicit, links between plant-based diets and the values people consider important and focus on removing constraints to encourage uptake of plant-based diets.